Comparison of selected aspects of caring for the patients with transradial and transfemoral approach for coronarography - Płaszewska-Żywko, Lucyna; Klecha, Lesława (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Background: Coronarography is a commonly used diagnostic procedure for ischaemic heart disease. Routinely, the femoral approach (FA) and, in the last years, also radial approach (RA) are used. The results of the studies abroad show benefits of using radial access for coronarography. In Poland, however, there is a limited number of publications on this subject and lack of studies on nursing care of the patients with different approaches for coronarography. The aim of the study was to determine positive and negative aspects of using FA and RA for coronarography with respect to patients’ comfort, difficulties in nursing care, complications and duration of hospital stay. Material and methods: One hundred and twelve patients (group A – 59 patients with FA, group B – 53 patients with RA) and 53 nurses were included into the study The questionnaire for the patients including sociodemographic data and questiones with Likert’s scale assessing difficulties with self-care was used. Pain intensity was evaluated by VAS scale. The length of hospitalisation and complications were analysed from medical records. Questionnaire for nurses included sociodemographic data and information about difficulties in caring for the patients with particular approach for coronarography. For statistical analysis t -Students test, x 2 test and Spearman correlation analysis were used. Results : In group B, the pain intensity was significantly lower (mean 1.9 +1.6 vs. 2.7 +2.2, p < 0.05) and the time of compression significantly shorter (5 h 42 min vs. 15 h 24 min, p < 0.05) when compared with group A. Patients from group B declared less discomfort during preparation for coronarography and self-care after that. Moreover, the length of hospitalisation was significantly lower in group B (3.0 +1.2 days vs. 5.0 +2.6 days, p < 0.05), so was the percentage of patients with complications. Nurses found the RA more advantageous with respect to nursing care. Conclusions : In nurses’ and patients’ opinions the radial access is more advantageous than femoral access.